Disability and Gender: Feminity of Physically Disabled Women - Šėporaitytė, Deimantė (Sociologija. Mintis ir veiksmas, 2006)
Analyzing twelve semi-structured interviews with physically disabled women and the data collected at the summer camp of the Lithuanian Paraplegia Association in Monciškės and at the show “Miss Disability 2005, the article focuses on the peculiarities of the disabled women’s femininity. The article also uses several texts from the Lithuanian nerve-muscle sickness journal “Nendrelė” and life stories of young disabled women published in the youth magazine “Panelė.” The interview material enables us to conclude that most physically disabled women perceive femininity traditionally. In their view, a capability to carry out “feminine” household duties, physical beauty and a “soft” character are the main features of a woman. Internalizing normative body ideals, most disabled young women attempt to disguise their disability. The informants encounter the society’s negative attitude towards them, particularly with regard to their sexuality and motherhood. However, the data of our research reveals that the real life of physically disabled contradicts the established public attitude towards them. Most of them consider sexuality and partnership as a normal part of their lives.